Social interaction in school advisory for school projects through e-learning - Castellanos Niño, Carlos Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This article arises from an on-going research, its aim is to study mediated social interaction through an e-learning platform, called: “CHAMILO”. This is a proposal to strengthen the pedagogical innovation in advising school projects. This project is carried out at Institución Educativa Departamental Tisquesusa of Susa town (Cundinamarca). The study develops an action research which begins with a preliminary case-study analysis and describes the textual communication and group work in the disclosure of important elements of social interaction within the virtual context. Later on, as a part of the strengthening of the teaching-learning processes of pedagogical innovation, it proposes a structure composed by a TIC infrastructure and textual communication competences, group work and the use of TIC, necessary to optimize the social interaction within e-learning.